2014
DOI: 10.1089/mdr.2013.0217
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Multidrug-ResistantEnterococcus faecalisWithin the Household Setting

Abstract: Advances in veterinary medicine have resulted in the survival of many animals with severe illness or infectious diseases. In addition, increased usage of antimicrobial agents for veterinary purposes has contributed to the worldwide problem of increasing antimicrobial resistance. The objective of this study was to contribute to better understand the potential and implications for the spread of antimicrobial-resistant enterococci between pets receiving antimicrobial treatments and their owners. Three household a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
2
13
1
Order By: Relevance
“…Although previous studies showed similarities between human and pet enterococci isolates (Damborg and others 2009, Kwon and others 2012, Leite-Martins and others 2014a), or resistance genetic determinants shared within households (Martins and others 2013), the present data failed to find any significant results for animals belonging to health professionals or people already exposed to AM treatments; this result may be explained by the low number of animals analysed in those groups (Table 2). …”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Although previous studies showed similarities between human and pet enterococci isolates (Damborg and others 2009, Kwon and others 2012, Leite-Martins and others 2014a), or resistance genetic determinants shared within households (Martins and others 2013), the present data failed to find any significant results for animals belonging to health professionals or people already exposed to AM treatments; this result may be explained by the low number of animals analysed in those groups (Table 2). …”
Section: Discussioncontrasting
confidence: 96%
“…In vivo transfer of VAN resistance genes from enterococci isolates of animal origin to enterococci isolates of human origin has already been demonstrated (Lester and others 2006). In Portugal, the same multidrug-resistant enterococci were isolated from pets and owners as well as from various commonly touched objects and surfaces from the household (Leite-Martins and others 2014a). …”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies suggest a link between antimicrobial use and the emergence of bacterial antimicrobial resistance (AMR) (1,2). Recently, the World Health Organization (WHO) designated AMR a major threat to public health (3) and evidence is accumulating that resistant bacteria can be transmitted between humans, food producing animals, and companion animals (4)(5)(6)(7). Antimicrobial stewardship (AMS) policies and practices aim to limit the development of AMR and improve patient outcomes by promoting the appropriate use of antimicrobial drugs (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, improvements in medical assistance have enabled pets to be treated in veterinary hospitals and subjected to antibiotic therapies very similar to the ones used in human medicine [2]. This reality coupled with the intimate contact that exists between pets and their owners and negligence in hygiene practices by humans [3], makes companion animals important players in the global dissemination of AMR. Even so, there still is a lack of information on the transfer of antimicrobial resistant strains from pets to humans and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent corresponding studies focusing on companion animals have started to be performed [8][9][10][11][12][13]. Since dogs and cats are kept in close contact with their owners, silent within-household transmission of resistant bacteria and resistance genes may occur in either direction by direct contact or, indirectly, through household surfaces and objects contaminated by feces, oral secretions or urine [3,14,15].…”
Section: Introductionmentioning
confidence: 99%